Parasitic Contamination of Consumed Vegetables from Farms in Ramhormoz - Leila Arab; Mahmoud Rahdar (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2012)
Background and Objective: Relatively large group of parasitic infections are transferred to human through water, soil and foodstuffs such as vegetables. Eating raw vegetables with edible food is common in nutritional habits among most Iranian societies. While providing a significant percentage of essential vitamins and materials, eating raw vegetables with inadequate disinfection conditions carries risk to infection various parasitic infections. The aim of this study was to understand the situation and type of contamination in farm vegetables of Ramhormoz city. Materials and Methods: In this descriptive cross-sectional study, 20 cultivated vegetables farms were selected from five area: north, south, west, east and centre of Ramhormoz Samples were examined using sediment concentration with anionic detergent. The total number of samples was 140. For data analysis, SPSS software was used. Results: The results showed that 49% of vegetables were infested with various pathogenic and nonpathogenic parasites. The highest infestations was associated with nematodes larva (44%) and the lowest were related to Hymenolepis nana (1/8%) and Trichostrongylus (1/8%).Conclusion: The findings of this study showed that the main sources for parasitic infestations in vegetables are from human compsites. Education of people on how to wash edible vegetables in areas where there is a parasitic infestations, can promote community health and effectively control parasitic diseases. In addition, the use of human compost in agriculture should be avoided.